Centralized and Decentralized Federal System: A Comparative Analysis of Governance Structures and Policy Implementation - Kharel, Aswasthama Bhakta; Acharya, Abinav (Interdisciplinary Journal of Management and Social Sciences, 2023)
A comparative analysis of centralized and decentralized federal systems with the exploration of their governance structures and the implications for policy implementation is conducted in this research. Centralized and decentralized systems with their attributes are studied and critically analyzed. By examining case studies from various countries, the research seeks to shed light on the strengths and weaknesses of each system and identify the factors that contribute to its effectiveness. The paper also delves into the distribution of powers, decision-making processes, fiscal arrangements, and the level of autonomy granted to subnational entities in both centralized and decentralized federal systems. The findings of this study offer insights into the dynamics of governance and policy implementation within federal systems, ultimately contributing to a deeper understanding of the relationship between centralized and decentralized approaches. It is found that even countries with a decentralized federal system acquire few characteristics of a centralized federal state and vice versa. Meanwhile, Nepal being a decentralized federal state hasn’t yet been able to maintain a complete decentralized governance system as many of the authorities and obligations are concentrated in the central government.